Thyroid dysfunction in Human immunodeficiency virus infected patients and their correlation with CD4 count - Porwal, Vipin; Deshpande, Rajesh; Jain, Aadish Kumar (International Journal of Research in Medical Sciences, 2021)
Background: The aim of this study was to evaluate the prevalence of thyroid abnormalities in a subset of human immunodeficiency virus positive patients. Methods: This was a cross-sectional prevalence study conducted on adult HIV positive patients. The patients presenting with hypertension, diabetes mellitus, coronary artery disease or thyroid disorder were excluded from the study. An exhaustive medical history and investigation using biochemical, microbiological and radiological tests were performed to confirm the diagnosis. Additionally, tests were done to determine the free T3, T4, thyroid stimulating hormone and CD4 cell count in all the patients. Results: The prevalence of thyroid dysfunction in our study was 45.7%. Various types of thyroid dysfunctions obtained were euthyroid sick syndrome in 18.6%, subclinical hypothyroidism in 11.4%, secondary hypothyroidism in 10% and primary hypothyroidism and hyperthyroidism each in 2.9% cases. As the stage of HIV advanced, there is alteration in the level of thyroid stimulating hormone, FT3 and FT4. A direct correlation was found between FT3 and CD4 counts but no correlation was found between thyroid stimulating hormone and FT4 levels and CD4 counts. Conclusions: A higher prevalence of thyroid dysfunction that was largely asymptomatic was observed in HIV infected patients with significant change in the hormonal levels in patients with low CD4 count. A direct correlation was observed between FT3 hormone level and CD4 count.